Pengaruh Faktor Produksi terhadap Produksi Usahatani Padi Sawah Tadah Hujan di Desa Menjalin - Delaseh, Seravico Singa; Yurisinthae, Erlinda; Kusrini, Novira (Department of Agribusiness, Halu Oleo University, 2020)
This study aims to analyze the factors that influence the production of rainfed lowland rice in Menjalin Village. The variables used in this study were the production of rainfed lowland rice, land area, seeds, urea fertilizer, KCL fertilizer, Gramoxon herbicide, Regent insecticide, and harvest labor. This type of research is a descriptive study with a qualitative approach. This research was conducted in Menjalin Village from March 2020 to April 2020. The population in this study amounted to 816.Sampling using a simple random technique with determining the number of samples using the Slovin formula so that the sample used in this study were 89 respondents. The analysis used is a linear analysis of the Cobb-Douglas production function. Adaptation used SPSS version 25. The results showed that simultaneously the area of land, seeds, urea fertilizer, KCL fertilizer, Gramoxon herbicide, Regent insecticide, and harvest labor affected the production of rainfed lowland rice farming in Menjalin Village. Whereas partially the area of land, seeds, urea fertilizer, and herbicide Gramoxon have a significant effect on the production of rainfed lowland rice in Menjalin Village, while KCL fertilizer, Regent insecticide, and harvest labor do not have a significant effect on the production of farmed lowland rice. rain in the village of Menjalin.